Asking Questions in a World of Answers - Vos, Matthew (Journal of sociology and Christianity, 2017)
Sociologists frequently raise difficult and uncomfortable questions in and about the organizations which they inhabit. Because institutions depend on full confidence in orthodox answers for their stability, the prophetic voice of question-raising sociologists can be threatening to the priestly class of institutional gate-keepers. Raising challenging questions in the face of reigning answers often puts sociologists at odds with institutional interests and certainty, and therefore they sometimes face marginalization by and even exclusion from the organizations and communities in which they live and work. This article examines some of the ways in which sociologists deal in the currency of questions, and explores the idea that certainty of absolute knowledge can undermine Christian faith, distort the meaning of the Biblical text, and reduce the sense of wonder, enchantment, and mystery that a life of faith can offer.